2008
DOI: 10.1111/j.1440-1827.2008.02221.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of neural stem progenitor cells in cytomegalovirus infection of the brain in mouse models

Abstract: Cytomegalovirus (CMV) is the most significant infectious cause of brain disorders in humans. Although the brain is the principal target organ for CMV infection in infants with congenital infection and in immunocompromised patients, little has been known about cellular events in pathogenesis of the brain disorders. Mouse models have been developed by the authors for studying the cell tropism, infectious dynamics of CMV infection and the effects of CMV infection on proliferation, regeneration and differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 102 publications
1
26
0
1
Order By: Relevance
“…Nevertheless, these animal models have provided evidence that the highest CMV susceptibility in CNS is presented by neural precursor cells (NPCs) (Tsutsui et al 2002). Infection of these cells might be the cause of microcephaly and mental retardation since it has been observed that murine CMV inhibits NPC proliferation and migration (Shinmura et al 1997;Tsutsui et al 2008). Furthermore, studies of functional neural cells after CMV infection, though scarce, reveal that infected cells have altered intercellular communication and deficient response to neurotransmitters (Ho and van den Pol 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these animal models have provided evidence that the highest CMV susceptibility in CNS is presented by neural precursor cells (NPCs) (Tsutsui et al 2002). Infection of these cells might be the cause of microcephaly and mental retardation since it has been observed that murine CMV inhibits NPC proliferation and migration (Shinmura et al 1997;Tsutsui et al 2008). Furthermore, studies of functional neural cells after CMV infection, though scarce, reveal that infected cells have altered intercellular communication and deficient response to neurotransmitters (Ho and van den Pol 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recientemente se le ha atribuido parte del daño causado por el virus a efectos sobre las CPN, al localizarse las cĂ©lulas infectadas, principalmente en las regiones ventricular y subventricular donde residen este tipo de cĂ©lulas. Se han relacionado algunas de las manifestaciones clĂ­nicas mĂĄs frecuentes con la infecciĂłn de las CPN, como la microcefalia que podrĂ­a tener su origen en la disminuciĂłn de su proliferaciĂłn y posterior migraciĂłn, asĂ­ como interfiriendo con procesos de diferenciaciĂłn en estas cĂ©lulas 58,66,67 . No obstante, son necesarios mĂĄs estudios que logren esclarecer los mecanismos que subyacen al daño en SNC inducido por el virus, asĂ­ como las consecuencias clĂ­nicas que estos efectos tengan.…”
Section: Conclusionesunclassified
“…Founder studies in the mouse revealed that HCMV murine counterpart, namely murine cytomegalovirus (MCMV), infected the developing brain the cerebral ventricular walls, a region known to contain neural progenitors. 6 Strikingly, infected cells seemed to migrate from the (sub-) ventricular zones to the cortical plate or the hippocampus. 6 Mouse neurons were also found to be sensitive to infection.…”
Section: Hcmv Tropism In the Developing Brainmentioning
confidence: 99%
“…6 Strikingly, infected cells seemed to migrate from the (sub-) ventricular zones to the cortical plate or the hippocampus. 6 Mouse neurons were also found to be sensitive to infection. Studies in human were limited for obvious reasons, and in vitro studies were performed with primary cultures of human brain cells prepared from deceased, uninfected fetus.…”
Section: Hcmv Tropism In the Developing Brainmentioning
confidence: 99%